The Effect of Green Supply Chain Management Practices on the Sustainability Performance of Turkish Shipyards - Tantan, Mehmet; Akdağ, Hatice Camgöz (MDPI AG, 2022)
The study explores the effect of green supply chain management (GSCM) practices on three sustainability dimensions; environmental, social, and economic in Turkish shipyards. The GSCM practices examined are green design, green purchasing, green production, green marketing, environmental management, and recycling. A research model was developed to test the relationship between six GSCM practices and the three sustainability performance dimensions by using a shipyard-level survey. Environmental uncertainty was placed in the model as a moderator variable. The authors utilized a web-based survey. Partial least squares structural equation modeling was used to test the proposed hypotheses. The research revealed that the GSCM practices were positively significant for economic and social performance but not for environmental performance. Environmental uncertainty did not have a moderating effect between GSCM practices and sustainability performances. Quality, Environmental, and Safety Certifications are the first step for GSCM practices but do not mean the company achieved environmental performance positively. The results brought into prominence the GSCM practices in improving the sustainability performance of the Turkish shipyards. While this study was the pioneer in examining the relationship between GSCM and sustainability performance in Turkish shipyards, it enhanced the understanding of GSCM practices and sustainability performances.
Keywords: sustainability performance; shipbuilding industry; Turkish shipyards; green supply chain; PLS-SEM